Stages of formation of innovation infrastructure: developed countries’ and Kazakhstan’s experience. (Journal of Economic Research & Business Administration, 2016)
In the rapidly developing world economic progress and development of the state as a whole is largely driven by the innovative potential of the country. In turn, the innovation infrastructure, which settles the direction of innovative development of the country, is a very complicated structure, the formation of which took more than a decade and still continues to sophisticate its elements. This article is closely studying the phenomenon of innovation and rapid development of its elements in the North Atlantic region, on the «homeland of innovations». This paper is based on the studies of Sh.Kungand and D.A.Kartsev: history and development of innovation infrastructure, general dynamics of the geographical spread of a new knowledge. Studies of Minat and Kovalev laid on the basis of this article, they outlined the three main stages of emergence of innovative infrastructure and development in the framework of the chronology of scientific and technological development, which describe not only emergence of individual elements, but also influence of the state regulations to them.
Keywords: innovation infrastructure; innovation infrastructure development; science parks; business-incubators; innovations; venture capital.